2020
DOI: 10.4038/jas.v15i2.8802
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Essential Oils and GRAS Compounds on Postharvest Disease Control in Mango (Mangifera indica L.cv Tom EJC)

Abstract: Purpose : Mango (Mangifera indica L. cv. Tom EJC) has a high economic value due to its unique qualities. Postharvest diseases such as anthracnose cause considerable loss of fruits in the market. Applications of synthetic fungicides are the common practice for controlling postharvest diseases, which could lead to hazardous effects on health. Therefore, search for alternative measures for the control of anthracnose are in demand. Research Method : Different fungal species have been described as causative agents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Moreover, when the fruit was placed in a potassium sorbate and hot water solution (55 • C for 5 min) and cooled in water, the disease severity was reduced without affecting the fruit quality. Kalupahana et al (2020) [153] tested the effectiveness of sodium bicarbonate and sodium metabisulfite against the mango anthracnose pathogen, C. siamense, and found that both salts inhibited mycelial growth.…”
Section: Present and Future Management Of Anthracnosementioning
confidence: 99%
“…Moreover, when the fruit was placed in a potassium sorbate and hot water solution (55 • C for 5 min) and cooled in water, the disease severity was reduced without affecting the fruit quality. Kalupahana et al (2020) [153] tested the effectiveness of sodium bicarbonate and sodium metabisulfite against the mango anthracnose pathogen, C. siamense, and found that both salts inhibited mycelial growth.…”
Section: Present and Future Management Of Anthracnosementioning
confidence: 99%
“…Even though, Türkkan and Erper (2012) highlighted that 0.40% (w/v) sodium metabisulfite could result in 100% inhibition of F. oxysporum, the same compound at 0.30% (w/v) concentration only achieved a 43.22% inhibition of the respective fungus during the present study. However, Kalupahana et al (2020) revealed that physicochemical properties of mango even treated with a low concentration (i.e. 0.15%) of sodium metabisulfite were the lowest among all treatments.…”
Section: Discussionmentioning
confidence: 92%
“…Carbonate salts have consistently demonstrated effective control over various postharvest fungi in fruits and vegetables, contributing to improved fruit firmness and reduced decay [45]. However, the precise mode of action of these salts in reducing postharvest diseases is not yet fully understood.…”
Section: Discussionmentioning
confidence: 99%